A Chromosome 7 Pericentric Inversion Defined at Single-Nucleotide Resolution Using Diagnostic Whole Genome Sequencing in a Patient with Hand-Foot-Genital Syndrome. - Christopher M Watson; Laura A Crinnion; Sally M Harrison; Carolina Lascelles; Agne Antanaviciute; Ian M Carr; David T Bonthron; Eamonn Sheridan (PLoS ONE)
Next generation sequencing methodologies are facilitating the rapid characterisation of novel structural variants at nucleotide resolution. These approaches are particularly applicable to variants initially identified using alternative molecular methods. We report a child born with bilateral postaxial syndactyly of the feet and bilateral fifth finger clinodactyly. This was presumed to be an autosomal recessive syndrome, due to the family history of consanguinity. Karyotype analysis revealed a homozygous pericentric inversion of chromosome 7 (46,XX,inv(7)(p15q21)x2) which was confirmed to be heterozygous in both unaffected parents. Since the resolution of the karyotype was insufficient to identify any putatively causative gene, we undertook medium-coverage whole genome sequencing using paired-end reads, in order to elucidate the molecular breakpoints. In a two-step analysis, we first narrowed down the region by identifying discordant read-pairs, and then determined the precise molecular breakpoint by analysing the mapping locations of "soft-clipped" breakpoint-spanning reads. PCR and Sanger sequencing confirmed the identified breakpoints, both of which were located in intergenic regions. Significantly, the 7p15 breakpoint was located 523 kb upstream of HOXA13, the locus for hand-foot-genital syndrome. By inference from studies of HOXA locus control in the mouse, we suggest that the inversion has delocalised a HOXA13 enhancer to produce the phenotype observed in our patient. This study demonstrates how modern genetic diagnostic approach can characterise structural variants at nucleotide resolution and provide potential insights into functional regulation.